Oral Iron Prophylaxis in Pregnancy: Not Too Little and Not Too Much! - Nils Milman (Journal of Pregnancy)
An adequate supply of iron is essential for normal development of the fetus and newborn child. Iron deficiency and iron deficiency anemia (IDA) during pregnancy increase the risk of preterm birth and low birth weight. Iron is important for development of the fetal brain and cognitive abilities of the newborn. Children born to iron-deficient mothers will start their lives suffering from iron deficiency or even IDA. Oral iron prophylaxis to pregnant women improves iron status and prevents development of IDA. The Danish National Board of Health has since 1992 recommended prophylactic oral iron supplements to all pregnant women and the currently advocated dose is 40–50 mg ferrous iron taken between meals from 10 weeks gestation to delivery. However, 30–40 mg ferrous iron is probably an adequate dose in most affluent societies. In developed countries, individual iron prophylaxis guided by iron status (serum ferritin) has physiological advantages compared to general iron prophylaxis. In contrast, in most developing countries, general iron prophylaxis is indicated, and higher doses of oral iron, for example, 60 mg ferrous iron or even more should be recommended, according to the present iron status situation in the specific populations of women of fertile age and pregnant women.